A Comparative Study of the Job Tasks, Functions, and Knowledge Domains of Rehabilitation Professionals Providing Vocational Rehabilitation Services in Australia and Germany. (January 2015) - Matthews, Lynda R.; Buys, Nicholas; Randall, Christine; Marfels, Britta; Niehaus, Mathilde; Bauer, Jana F.
Vocational rehabilitation services have been implemented in a number of countries to facilitate the return to work of sick and injured workers, yet little research has been undertaken to document competencies required to provide services globally. This study compared the job tasks, functions, and knowledge domains deemed important by Australian and German rehabilitation professionals working in vocational rehabilitation settings to identify common practice domains. An online survey comprising items from the Rehabilitation Skills Inventory–Amended and the International Survey of Disability Management was completed by 149 Australian and 217 German rehabilitation professionals. Items from each measure were submitted to factor analysis, using principal axis factoring as the extraction technique. Three common domains were identified: (a) vocational counseling, (b) workplace disability case management, and (c) workplace intervention and program management. Differences in skill and knowledge domains centered on the levels of specialization in vocational rehabilitation practices in each country. Ongoing transnational research is required to ensure that a "global curriculum" covers core competencies, while at the same time allowing for specialization at a local level.